Vengefulness Evolves in Small Groups - Daniel Friedman; Nirvikar Singh (University of California, Economics Department, 2004)
We discuss how small group interactions overcome evolutionary problems that might otherwise erode vengefulness as a preference trait. The basic viability problem is that the fitness benefits of vengeance often do not cover its personal cost. Even when a sufficiently high level of vengefulness brings increased fitness, at lower levels, vengefulness has a negative fitness gradient. This leads to the threshold problem: how can vengefulness become established in the first place? If it somehow becomes established at a high level, vengefulness creates an attractive niche for cheap imitators, those who look like highly vengeful types but do not bear the costs. This is the mimicry problem, and unchecked it could eliminate vengeful traits. We show how within-group social norms can solve these problems even when encounters with outsiders are also important.
Keywords: 330